(untitled) (Ustozlar uchun, 2026)
This study examines how work-life balance affects the productivity of employees working in a hybrid environment after the pandemic. The pandemic has made a big difference in the conditions of many people, in particular their personal lives and work. Many people started working from home. In the office, it’s hard to know when to work and start your personal life. It really affects how people feel and how well they do their job. The purpose of this study is to find out how work-life balance affects people’s work. To conduct this study, a combination of figures obtained from a survey and interviews with employees was used. When people have a work-life balance, they do their job better. They feel stressed, satisfied with their work, and take more care of themselves. Employee productivity is the key to any company’s success. It is influenced by factors such as the degree of employee satisfaction with their work and the level of stress they experience at work. Stress at work depends on how much pressure an employee feels at work. To understand the big picture, I talked to people from different professions. The survey helped to understand how work-life balance is also related to productivity. In this way, this research can help companies improve the work of their employees, help them do their jobs better and make them happier, and help companies make plans for their employees.